2022
DOI: 10.1007/s42532-022-00119-5
|View full text |Cite
|
Sign up to set email alerts
|

Using researcher and stakeholder perspectives to develop promising practices to improve stakeholder engagement in the solutions-driven research process

Abstract: Translational approaches to science have the potential to produce research that better meets the needs of community stakeholders and advances scientific understanding. Researchers involved in translational research make committed efforts to increased engagement and communication with stakeholders throughout the research process, from planning through implementation and evaluation. Referred to as solutions-driven research within the U.S. Environmental Protection Agency (EPA) Office of Research Development, this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Several studies have shown that stakeholder characteristics determine the decision-making process and development process. The community has much discussion but only involves citizens who are most motivated and voluntarily to participate, involving people who are better off in terms of income, education, and status [50][51][52][53][54][55][56].…”
Section: Factors Affecting Stakeholders' Communication In Pdpmentioning
confidence: 99%
“…Several studies have shown that stakeholder characteristics determine the decision-making process and development process. The community has much discussion but only involves citizens who are most motivated and voluntarily to participate, involving people who are better off in terms of income, education, and status [50][51][52][53][54][55][56].…”
Section: Factors Affecting Stakeholders' Communication In Pdpmentioning
confidence: 99%
“…To evaluate the effectiveness of this new approach to engagement, social scientists were engaged from the start of the project to its completion to capture the experience of the various stakeholders. These researchers used formative (mid-project) [Canfield, Mulvaney & Chatelain, 2022] and end-of-project data collection methods including autoethnography, content analysis, and semi-structured interviews with researchers and external stakeholders.…”
Section: Introductionmentioning
confidence: 99%
“…We then describe the methods used in our internal evaluation, including how the formative evaluation results were incorporated into the ongoing project. We next compare the results of the interviews held at the end of the project with those conducted mid-project [Canfield et al, 2022]. We finally discuss the value of internal two-stage evaluation, and lessons learned to improve future transdisciplinary projects using evaluation of science communication and public engagement with research.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we analyze the process to respond to recent calls to provide recommendations for effective stakeholder‐driven, translational environmental research in the U.S. (Canfield et al. 2021). We do this by asking, what are opportunities and challenges in stakeholder‐driven, translational research in fluvial geomorphology‐informed flood management in the United States?…”
Section: Introductionmentioning
confidence: 99%
“…This article taps into a decade-long, stakeholder-driven process in Massachusetts, USA that attempted to reprioritize river flood management by giving rivers room to move. Here, we analyze the process to respond to recent calls to provide recommendations for effective stakeholder-driven, translational environmental research in the U.S. (Canfield et al 2021). We do this by asking, what are opportunities and challenges in stakeholder-driven, translational research in fluvial geomorphology-informed flood management in the United States?…”
Section: Introductionmentioning
confidence: 99%